Dispensasi Kawin dan Perkembangannya: Fenomena Perzinahan di Kabupaten Banyumas - Muflichah, Siti; APHA, Journal Manager (Asosiasi Pengajar Hukum Adat (APHA) Indonesia, Fakultas Hukum Universitas Trisakti - Jakarta Barat, Indonesia, 2018)
This study aims to analyze developments regarding marriage dispensation associated with Law Number 36 of 2009 concerning Health and Law Number 35 of 2014 concerning Child Protection. The subjects of this study were the authorities and related directly and indirectly to the determination of marriage dispensation in the Purwokerto Religious Court and the Banyumas Religious Court. Data collection is done by direct interviews with resource persons to obtain more in-depth and precise results. Analysis of the data used in this study is descriptive qualitative. Withdrawal of conclusions is done inductively, namely from empirical data and facts in the field, after analysis is then drawn conclusions. The results of the study indicate that Article 7 of Law Number 1 of 1974 concerning Marriage and marriage dispensation collided with Article 1 number 1 of Law Number 35 of 2014 concerning Amendment to Law Number 23 of 2002 concerning Child Protection concerning the age of children and Article 26 paragraph 1 point c of Law Number 23 of 2002 concerning Child Protection which states that parents are obliged and responsible for preventing the occurrence of marriage at the age of children. Based on the health aspect, the age limit of marriage is a guarantee that the prospective husband and wife has cooked their soul, so that they can realize the goals of marriage well without ending divorce and getting good and healthy offspring in accordance with Article 72 of Law No. 36 of 2009 about health.